(untitled) (Journal of Parents and Teachers, 1996)
Sexuality and love are addressed through a poetic approach, highlighting the relevance of dialogue and emotional connection. The figure of the “man-tube”, which represents a disconnected sexuality, is contrasted with the “man-tree”, which symbolizes the integration of love and tenderness. In addition, reflective questions are proposed to stimulate discussion about relationships and human needs.